2012
DOI: 10.1007/s11262-012-0834-6
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of SYBR green-based qPCR assay for rapid evaluation and quantification for anti-Hantaan virus compounds in vitro and in suckling mice

Abstract: Hantaan viruses cause two severe diseases lacking efficient treatment, yet no effective prophylactic vaccines are available. Continued exploration of alternative antiviral agents to treat hantavirus-related syndromes remains compulsory. The fluorescence-based quantitative real-time PCR (qPCR) has become the touchstone for target gene quantification. In the present study, standard curves for Hantaan virus (HTNV), mouse, and human glyceraldehyde-3-phosphate dehydrogenase (GAPDH) were generated by serial 10-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Despite Brazil being considered free of HPAI, surveillance of AIV in migratory birds remains incomplete in that country, and AIV data remain scarce. Although H6N1 viruses are considered low‐pathogenic, an isolate of this subtype, albeit genetically distinct from our isolates, has been isolated from a human infection in Taiwan 46. Regardless of the zoonotic potential of the viruses found in Lagoa do Peixe National Park, increased surveillance in all animal species in the country is prudent.…”
Section: Discussionmentioning
confidence: 83%
“…Despite Brazil being considered free of HPAI, surveillance of AIV in migratory birds remains incomplete in that country, and AIV data remain scarce. Although H6N1 viruses are considered low‐pathogenic, an isolate of this subtype, albeit genetically distinct from our isolates, has been isolated from a human infection in Taiwan 46. Regardless of the zoonotic potential of the viruses found in Lagoa do Peixe National Park, increased surveillance in all animal species in the country is prudent.…”
Section: Discussionmentioning
confidence: 83%
“…Since these studies were performed by only one research group, with a limited number of animals, they should be reproduced by others before concluding to a beneficial effect of ARB against hantavirus infection. However ARB efficacy compared well in vivo with that of ribavirin, the reference treatment for such a disease (Wei et al, 2013).…”
Section: Viruses Causing Hemorrhagic Fever and Encephalitismentioning
confidence: 99%
“…Recently, Chinese studies demonstrated antiviral activity of ARB against the Hantaan virus, an enveloped virus from the Bunyaviridae family Wei et al, 2013), causing an often lethal hemorrhagic fever with renal syndrome (HFRS). In vitro, ARB was more efficient when added before infection, with an IC50 in the 2 lM range.…”
Section: Viruses Causing Hemorrhagic Fever and Encephalitismentioning
confidence: 99%
“…All reactions were performed in at least duplicate for each sample. The relative mRNA expressions were normalized to the level of GAPDH and were calculated using the formula as described elsewhere [25].…”
Section: Apoptosis-related Genes Isolation and Real-time Rt-pcrmentioning
confidence: 99%